Invoking “Indigenous Circumstances” in Disaster Governance Implications for Disaster Justice - Macalandag, Regina; Philippines (Archīum Ateneo, 2024)
In 2010 the Philippine government introduced a national policy aiming forsafer, adaptive, and disaster-resilient communities. Thisarticle questionsthe assumption that the policy inherently benefits everyone in disastergovernance. Focusing on the challenges faced during its implementation,particularly in the resettlement of sea-based Badjao indigenous peoplenow living in urban areas, the study draws on a 2018–2019 case study. Itreveals that the rhetoric of safety justifies resettlement, contrasting withthe lived experiences that contest risk reduction, and argues that state-ledresettlement intensifies vulnerabilities. Utilizing empathic recognition, thisarticle explores how neglecting empathy toward indigenous communitiescan lead to disaster injustice.KEYWORDS: INDIGENOUS PEOPLES • BADJAO • RESETTLEMENT • RHETORIC OFSAFETY • DISASTER JUSTICE